The Ignorance of Job - Shields, Martin A. 1965- (2020)
This paper argues that Job's response to Yhwh's speeches is best understood to be a recognition of Job's ignorance which results from a new-found appreciation for the complexity of creation that had been revealed to him in those speeches. Rather than Job repenting, he at last finds comfort in the realisation that his suffering and loss did not inevitably imply that Yhwh was unjust.